Lone males: Solitary and group‐living male howler monkey (Alouatta palliata) behavioral ecology in a Costa Rican rainforest - Bolt, Laura M.; Cavanaugh, Maeve N.; Schreier, Amy L. (American journal of physical anthropology, 2021)
Objectives Many group‐living primate species have evolved the capacity for some individuals to live alone for part of their lives, but this solitary life stage has rarely been the subject of focused research. The mantled howler monkey (Alouatta palliata) is a social primate species with bisexual dispersal that lives in mixed‐sex groups with low male‐to‐female sex ratios. Consequently, males often spend a long period of their lives as solitary individuals. This study compares the tree use, feeding, and long‐distance vocalization behavior of solitary and group‐living mantled howler monkey males living within a fragmented rainforest in Costa Rica, La Suerte Biological Research Station. Based on differences in competitive ability between solitary and group‐living males, we predicted that lone males would be found in significantly smaller feeding and resting trees, consume more low‐quality foods, and produce shorter howling bouts made at lower rates than group‐living males. Materials and methods We collected data on tree use and feeding during 30‐min focal samples on male focal animals, recording data at 2‐min intervals. We measured the trees in which the monkeys fed and rested for two or more intervals, and recorded the plant parts consumed. We recorded howling behavior using all‐occurrences sampling. Results Lone males used significantly smaller feeding and resting trees, consumed more low‐quality foods, and howled at lower rates but had longer howling bouts triggered by anthropogenic noise more than group‐living males. Discussion Our results demonstrate that lone males differ in their behavioral ecology compared to group‐living males, thus improving understanding of the solitary male life stage in primates. Lone male monkeys fed and rested in trees with smaller diameter at breast height than group‐living males. Lone males ate fallback foods like vines and stems more than predicted by chance. Lone males produced longer howls at lower rates than group‐living males.